Pengaruh Substitusi Tepung Ampas Kelapa (Cocos Nucifera L.) Terhadap Serat Pangan, Daya Kembang, Karakteristik Kimia Dan Tingkat Kesukaan Bolu - Sri O. Pusungulena; Erny J. N. Nurali; Jan R. Assa (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
Sponge is a popular snack product and is in great demand by all circles, starts from children to adults. Sponge cake with stick dough made from flour, sugar, eggs and far. The purpose of this study was to evaluate dietary fiber, swelllability, chemical characteristics and level of preference for sponge cake substituted with coconut dregs flour. This study used a competely randomized design method (CRD) method which consisted of 5 treatments and 3 repetitions, whit formulation of the use of coconut dregs flour and wheat flour in this study was in the A1 Theatment of 0% coconut dregs flour + 100% wheat flour. Treatment A2 5% coconut dregs flour + 95% wheat flour. Treatment A3 10% coconut dregs flour + 85% wheat flour, and A5 treatment was 20% coconut dregs flour + 80% wheat flour. Then an analysis of swellability, dietary fiber, nutrition content and organoleptic tests was carried out to determine the level of preference of the panelists. The results showed that the substitution of coconut dregs flour in sponge products had on significant effect on the swellability of the sponge and the level of preference of the panelists. The result of the analysis of the total food fiber of the sponge cake ranged from 11,65%-17,84%, soluble dietary fiber 3,50%-6,83% and insoluble dietary fiber 4,82%-13,62%. The level development of the sponge cake with an average value of 42,33-59,37. Water content 21,01% maximum SNI of 40%, ash content 0,92% maximum SNI of 3%, fat content 13,22% maximum SNI of 3%, protein content 7,33% and carbohydrate content 41,48%. In this study the most preferred treatment (Based on the highest average value on the scent and texture attributes because the results of the analysis of variance had no significant effect) according to the organoleptic tests was treatment A4 (15% coconut dregs flour : 85%) wheat flour with an assessment of color, taste, scent and texture. Keywords: Sponge; coconut dregs flou; dietary fiber; development rate; substitution